The Status of Equal Opportunities Ombudsman in the Republic of Lithuania: Selected Problematic Issues - Žalėnienė, Inga; Grigolovičienė, Danguolė (University of Wroclaw. Faculty of Law, Administration & Economics, 2014)
The present article aims at discussing the legal force and types of decisions adopted by the Equal Opportunities Ombudsman’s Office, which is the main body supervising implementation of the principle of equality in Lithuania. It is a paradox, but in the Lithuanian legal system there is no definite attitude regarding the legal effects of the Ombudsman Office’s decisions, and frequently the question of whether these decisions can be appealed against is raised. With uncertainty existing in the Lithuanian legal community, a controversial situation has arisen in which the decisions of the Ombudsman are challenged to administrative courts or to the Chief Administrative Disputes Commission, although the activity of the Equal Opportunities Ombudsman’s Office as an Ombudsman’s body is characterised by ‘the force of law’ and is not subject to appeal. The main task of this paper is to determine the legal force of the Equal Opportunities Ombudsman‘s decisions and the possibility of challenging them. For this purpose it is intended to: 1) analyse the fundamental regulations of activities undertaken by the Equal Opportunities Ombudsman’s Office; 2) identify the main types of decisions taken by the Equal Opportunities Ombudsman; 3) determine the legal force of those decisions and the possibilities to appeal against them from the perspective of positive law. The main conclusion of our research is that the Office of the Equal Opportunities Ombudsman can issue only one type of judicially binding decision, which declares an individual guilty of committing a violation of administrative law violation for which administrative sanctions may be imposed. Judicially non-binding decisions of the Ombudsman have the official status of written evidence and can be used in civil and administrative proceedings when questions of of illegal dismissal and salary reductions arise, as well as other issues related to violations of the equality principle. It should be noted that such decisions by the Ombudsman should not be contested, despite the contrary practice of ourts. The authors of the article maintain that the decisions adopted by the Equal Opportunities Ombudsman’s Office are recommendatory in nature and must be respected and implemented in good faith.
Keywords: Litwa; Biuro Rzecznika Praw Obywatelskich